Аналіз методів дозування рідин - Мігаль, С. Д. (ХНУРЕ, 2024)
This paper is dedicated to the analysis of liquid dispensing methods. Each method was analysed separately. In various industries, there is a need to automate the production process. This is due to the desire to improve product quality and speed up production. Sensors and microcontrollers are used to determine the amount of liquid in a container and its flow rate. Depending on the dosing method, appropriate sensors are used, the information from which is fed to a control device, such as a microcontroller. A microcontroller can provide automated control and dosing of liquid through pumps.
Keywords: метод дозування; точність дозування рідин; дозатори рідин